Impulsive Buying Berbelanja Online pada Mahasiswi Ditinjau dari Kecerdasan Emosional - Alitani, Mikaela Berliyana; Adzlin Alfianti (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Online shopping is the process of buying and selling goods and services through the internet. The convenience obtained in the online shopping process tends to be one of the triggers for impulsive buying. Impulsive buying is the tendency to buy spontaneously, immediately, reflectively and without paying attention to the consequences. Teenage girls, especially college students, seem to be more impulsive in shopping online. One of the factors that led to this impulsive buying was emotional intelligence. Therefore, this study aims to look at impulsive buying online shopping in college students in terms of emotional intelligence. This type of research is quantitative non-experimental, the sampling technique is purposive sampling involving 100 female students aged 17 to 24 years. The data analysis test is kendall tau_b correlation test technique, sig value (p) = 0.000 (p < 0.05) with a correlation coefficient (r) -0.759. So it can be concluded that there is a significant negative relationship between emotional intelligence and impulsive buying in online shopping. This study also showed the results of categorization that is : female students who have impulsive buying with high categorization as much as 26%, medium category 54% and low category as much as 20%.